The supporting tool for c programming in teaching and learning environment: An enhancement of hyperbook and course management system (CMS) / Syarilla A. Saany …[et al.] - A. Saany, Syarilla; A. Rahman, M. Nordin; Awang, M. Khalid; M. Zin, Abdullah; Salleh, Syahanim; Abdullah, Salwani (2004)
The use of Hyperbook concept in the teaching and learning of C Programming has previously been developed in several higher educational institutions, which acts as notes or reference. The development of Hyperbook was based on the traditional book learning format. While this application is primarily developed for students, another application has also been developed for instructors, known as CMS (Course Management System). CMS helps instructors to properly organize and manage courses. Starting with the registration of students, assessment of assignments and also assignment grading can be executed by CMS. The integration of the two packages, Hyperbook and CMS, will provide a total solution system which will further enhance the effectiveness and efficiency of the teaching and learning processes. Upgrading has been done to both packages so that the application can be adapted in the learning of C Programming as well as support ing the smoothness of management process on the part of the instructors. The upgraded packages will also help in the management process for the instructors. This paper will introduce the enhancement of the student module, the Hyperbook so that it will not only be used as a reference but also useful for doing exercises, mailing capabilities, facilities for upgrading exercises or notes and also facilities for receiving assignments from instructors. The instructor module on the other hand, will be furnished with the capabilities of receiving, marking and grading programming assignments. The deliverable will be a package that can be adapted in the teaching and learning process of C Programming thus making a leap from a traditional learning process to a digital learning experience